Hard times and European youth. The effect of economic insecurity on human values, social attitudes and well‐being. (21st September 2016) - Reeskens, Tim; Vandecasteele, Leen
Abstract : While economic downturns have adverse effects on young people's life chances, empirical studies examining whether and to what extent human values, social attitudes and well‐being indicators respond to sudden economic shocks are scarce. To assess the claim that human values are less affected by economic shocks than social attitudes and well‐being, two distinct yet related studies based on the European Social Survey (ESS) are conducted. The first employs a fixed effects pseudo‐panel analysis of the 2008–2014 ESS‐waves to detect whether changes over time in the socio‐demographic group's unemployment risk and national youth unemployment affect individual dispositions to varying degrees. The second study captures micro‐ and cross‐national effects in the 2010 ESS cross‐section. Unique for this set‐up is that we can test whether the findings hold for over‐time changes in youth unemployment within countries (pseudo‐panel), as well as for cross‐country differences in youth unemployment (multilevel). Both studies indicate that political trust, satisfaction with the economy and subjective well‐being are lowered by economic risk and hardship, while social trust and self‐rated health are less affected by changes in youth unemployment. Secondly, human values are immune to economic risk, underscoring that values transcend specific situations and are therefore resistant against sudden economic shocks.